THE MYTH OF AMERICAN DREAM IN GABRIELE MUCCINO'S THE PURSUIT OF HAPPYNESS: A SOCIOLOGICAL APPROACH - HAYULILININGSIH, RINA (2011)
The problem of this study is how the myth of American Dream is reflected in Gabriele Muccino’s The Pursuit of Happyness. The objective of this study is to analyze the movie based on the structural elements and to reveal the myth of American Dream in this movie based on the sociological approach. This study belongs to qualitative method. The data of the research are text and image consists of words, phrases, and sentences in The Pursuit of Happyness movie which is directed by Gabriele Muccino. Whereas the data source, there are two types, namely primary and secondary data source. The primary data source is the form of the manuscript of the movie itself, meanwhile the secondary data sources are taken from the books, journals, articles and internet which have related to this study. The method of the data collection is documentation. The technique of the data analysis is descriptive analysis. Based on the analysis the researcher draws several conclusions. The conclusion reveals the relationship between the movie and the social reality in America. First, the structural elements are related with social realities in historical background in order to find the resolution toward Gabriele Muccino’s The Pursuit of Happyness. Second, Gabriele Muccino describes his world view on how myth of American Dream reflects on American society in the late twentieth and early twenty-first centuries.